Measuring EFL Students` Vocabulary Size: Why and How - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2016)
Students` vocabulary size plays very important role toward their success in learning new language. To succeed in language learning 2,000 word families is often mentioned.  Having this number, a reader can understand nine from ten words in many written text. Right now, researchers propose number at least 3000 word families and mastering minimum 3000 word families will support students` success in academic reading at university level. To pass tests such as Cambridge First Certificate, TOEFL or IELTS. Vocabulary of 5,000 words are needed. Undergraduate non-native speaker of non-European countries could study successfully in English speaking countries by having word families around 5,000-6,000. A non-native speaker can study PhD level well with vocabulary about 9,000.  This article also will discuss the techniques to estimate someone vocabulary size.